Hubungan Status Gizi terhadap Perkembangan Motorik Kasar Anak Usia Dini - Nurhasanah Bakhtiar; Winda Trimelia Utami; Febi Liza Rindhani (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2022)
This study aims to determine the relationship between nutritional status and gross motoric development of children aged 3-5 years in Al-Rasyid Kindergarten, Marpoyan Damai District, Pekanbaru. The subjects of this study were the children of Al-Rasyid Kindergarten, Marpoyan Damai District, Pekanbaru. The object was the relationship between nutritional status and gross motor development of children aged 3-5 years. The population of this research is 16 children. The data collection techniques used were observation, interview, and documentation. Data processing techniques are using editing, coding, scoring, tabulating, and data entry. The data analysis technique used product moment correlation by calculating the t test using the SPSS Windows ver.16 program. The results of this research can be seen from the results of data analysis that the price of tcount = 2.047 and at α = 0.05 (5%) with df = 14 and ttable = 2.144. Because tcount = 2.047 <ttable = 2.144, it can be concluded that Ha is accepted and Ho is rejected, which means that in this study there is a significant relationship between nutritional status and gross motor development of children aged 3-5 years in Al-Rasyid Kindergarten, Marpoyan Damai District, Pekanbaru.Keyword: Nutritional Status, Gross Motor Development, Early Childhood